The Use of Picture Story Books Containing Social Issues as Learning Media for Fifth Grade Students of SD 71 Embacang Gedang - Iga Salpia; Minnah El Widdah; Ika Panggih Wahyuningtyas (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
This research was motivated by the low critical thinking skills of fifth-grade students at SD 71 Embacang Gedang. The initial condition showed that learning mastery in the pre-cycle stage only reached 26%. Students were still less active in the learning process, had difficulty analyzing problems, and were not accustomed to expressing their opinions logically. This study aimed to describe the learning process and improve students’ critical thinking skills through the use of picture storybooks containing social issues. The method used was Classroom Action Research (CAR), conducted in two cycles consisting of planning, implementation, observation, and reflection stages. The research subjects were 19 students. Data were collected through observation, interviews, documentation, and tests. The results showed a gradual improvement in students’ critical thinking skills. Learning mastery increased from 26% in the pre-cycle to 68% in the first cycle and 84% in the second cycle. Student and teacher activities also improved during the learning process.